Correlation between Surface Energy and Adhesion Force of Polyethylene/Paperboard: A Predictive Tool for Quality Control in Laminated Packaging - Danielle M. F. Madeira; Osvaldo Vieira; Luís Antonio Pinheiro; Benjamim de Melo Carvalho (International Journal of Chemical Engineering)
Poor adhesion continues to be a problem for manufacturers of laminated packaging. Therefore, the aim of this research was to study the effect of flame treatment, the type of coating, and starch application on the adhesion force of polyethylene/paperboard. The force of adhesion was determined using the peel test method; the paper surface energy was assessed by contact angle analysis; and paperboard roughness was determined by profilometer. The flame treatment did not affect the surface roughness but significantly increased the paperboard surface energy. The paperboard coated with polar latex showed much higher surface energy than the paperboard coated with nonpolar latex. The adhesion force of polyethylene presented a linear correlation to the surface energy of the paperboard. Therefore, the surface energy of paperboard is an excellent indication of its adhesion force to polyethylene, and this represents a very reliable and practical method in terms of quality control in the paper industry for producing laminated packages.